Analisis Kinerja Metode Fuzzy Teroptimasi PSO untuk Strategi Kendali MPPT pada Sistem Solar Photovoltaic - Soesanti, Indah; Syahputra, Ramadoni (Jurnal Teknik Elektro, 2021)
A fuzzy control system has been widely used in various problem solving. Its performance can be optimized using particle swarm optimization (PSO). This performance can be proven by applying it to the maximum power point tracking (MPPT) control strategy on solar photovoltaic systems. Solar photovoltaic power generation systems are increasingly popular because they are clean and renewable energy sources. The power generated by solar photovoltaic is strongly influenced by solar irradiation and the load carried. In order to obtain maximum power output, an MPPT control strategy is needed. An MPPT control strategy based on fuzzy and PSO hybrid control systems is proposed in this research. The fuzzy-PSO method selects and produces the optimal duty cycle for the boost dc-dc converter in a solar photovoltaic system. Variable duty cycle due to solar irradiation and load changes can be conditioned by the fuzzy-PSO-based MPPT method to extract maximum power. The research results show that the fuzzy-PSO method can control the solar photovoltaic output voltage through a dc-dc converter to produce maximum power at various solar irradiations. Test result by applying a resistive load produces output power at the maximum point. The best result is obtained in the 100 Ohm load test: the response time of 0.0818 seconds and excellent robustness.